Response of 25 Hybrid Maize Against Salinity Stress and Their Performance in Coastal Area - Meko Gustian; Rustikawati Rustikawati; Widodo Widodo; Catur Herison (Badan Penerbitan Fakultas Pertanian (BPFP), 2019)
Plant stress due to NaCl compound will have an impact on the reduction of plant growth and yield. Tolerant varieties are required to increase plant production in coastal areas since these areas are closely related to salinity. This study aimed to (1) determine the appropriate NaCl concentration for saline tolerance in maize stress selection, (2) determine the response of maize plant to salinity stress in nutrient culture, and (3) determine the response of new hybrid maize having adaptibility in coastal area. Two experiments were run from November 2017 until May 2018. The first experiment was conducted in a greenhouse at the Laboratory of Agronomy, Faculty of Agriculture University of Bengkulu to determine the tolerance response of 25 new hybrid maize to salinity in nutrient culture. The second experiment was conducted on the coastal areas in Beringin Raya Village, Muarabangkahulu District, Bengkulu City to determine the response of new hybrid maize having adaptibility in a coastal areas. The concentration of NaCl at which level the LC50 was determined was found to be in 150 mM. This concentration was then used to test the tolerance of 25 new hybrid maize to NaCl stress. The hybrids of CT18, CT19, CT22, CT25, CT31, CT33, CT34, CT40, CT47, and CT50 showed good responses to the concentration treatment of 150 mM NaCl based on plant fresh weight and shoot dry weight. The hybrids of CT17,CT19, and CT20 showed good adaptibility on coastal area based on the length of cob, diameter of cob, seed weight per cob, and cob weight per plant. Among those three hybrids, CT17 and CT20 resulted low fresh weight and low shoot dry weight. The factors other than NaCl in coastal area maybe affect better response. However, CT19 proved as a hybrid which was consistently in a good response to salinity stress both in nutrient culture and in coastal growing area.